DISPARITY OF SOCIAL CLASSES IN JAMES CAMERON'S TITANIC: A MARXIST APPROACH - SUPRIYANTI , DWI (2007)
The research is proposed to analyze the disparity of social classes in Titanic by James Cameron using Marxist approach. There are two objectives, the first is to analyze the film in term of the structural elements and the second is to analyze disparity of social classes in Titanic James Cameron's based on the Marxist perspective. This study is a qualitative study using the film of Titanic by James Cameron as the object of analysis of the study. There are two kinds of data sources: primary and secondary data. The primary data source is the DVD of the Titanic film and secondary data are some information from books, article, and website related to the subject. The method of collecting data in the research is the library research by summarizing, paraphrasing and documenting the data. In analyzing the data, the writer employs descriptive analysis. The outcome of the study shows that the film illustrates the disparity of social classes, the condition of the upper class and lower class in the late of twentieth century. The solution of the disparity problem equalizes both the upper class and lower class.